2018
DOI: 10.9738/intsurg-d-15-00205.1
|View full text |Cite
|
Sign up to set email alerts
|

Lauren Histology and Lymphatic Permeation are Critical Prognostic Factors in Borrmann Type I Gastric Cancer

Abstract: Lauren histology and lymphatic permeation are critical prognostic factors in Borrmann type I gastric cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Among them, type IV gastric cancer is most common to invade the serosa and the surrounding organs. Previously, when Borrmann type IV patients were treated, more than 70% of the patients belonged to the pT4a stage, and nearly 20% of the patients belonged to the pT4b stage (35). With the recent advances in CT imaging technology, the ability of CE-CT imaging to distinguish between the 5-layer structure of the gastric wall has significantly improved (36).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, type IV gastric cancer is most common to invade the serosa and the surrounding organs. Previously, when Borrmann type IV patients were treated, more than 70% of the patients belonged to the pT4a stage, and nearly 20% of the patients belonged to the pT4b stage (35). With the recent advances in CT imaging technology, the ability of CE-CT imaging to distinguish between the 5-layer structure of the gastric wall has significantly improved (36).…”
Section: Discussionmentioning
confidence: 99%
“…Among these macroscopic types showing better prognosis, Type I gastric cancer is reported to be relatively rare accounting for 2.2%‐8% of all resectable gastric cancer . Its detailed prognostic features remain unclear because few prognostic analyses have been carried out.…”
Section: Therapeutic Strategies According To Macroscopic Classificatimentioning
confidence: 99%
“…Its detailed prognostic features remain unclear because few prognostic analyses have been carried out. We recently investigated prognostic factors in Type I gastric cancer and reported that patients with a high risk for recurrence had diffuse‐type histology with robust lymphatic invasion . Recurrence pattern of Type I gastric cancer with intestinal‐type histology is unique as this type of gastric cancer is prone to metastasize to the liver such as colorectal cancer (CRC).…”
Section: Therapeutic Strategies According To Macroscopic Classificatimentioning
confidence: 99%